The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1016/j.clnu.2018.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Early energy and protein intakes and associations with growth, BPD, and ROP in extremely preterm infants

Abstract: Early provision of energy and protein may reduce postnatal weight loss and risk of morbidity in extremely preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
48
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 32 publications
(28 reference statements)
6
48
0
1
Order By: Relevance
“…For this reason, and because the consequences of the energy deficit are cumulative, we quantified the overall energy provided in this period. Previous studies have reported that newborns with BPD have a lower growth rate than those with no BPD and that this difference extends beyond the period of hospital stay (33,34) . In our study, too, the newborns with BPD presented a decrease in the weight gain curve at 1 week of life, with significantly lower z-scores.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…For this reason, and because the consequences of the energy deficit are cumulative, we quantified the overall energy provided in this period. Previous studies have reported that newborns with BPD have a lower growth rate than those with no BPD and that this difference extends beyond the period of hospital stay (33,34) . In our study, too, the newborns with BPD presented a decrease in the weight gain curve at 1 week of life, with significantly lower z-scores.…”
Section: Discussionmentioning
confidence: 95%
“…Some randomised clinical trials have not observed reduction in BPD with parenteral solutions with a higher energy content (46) or reduction in lung morbidity with early PN or higher energy content (47) , although it might be objected that the sample size in both clinical trials may not be adequate. Klevebro et al, through a cohort study, observe that early provision of energy and protein may reduce postnatal weight loss and risk of BPD in extremely preterm infants (33) .…”
Section: Discussionmentioning
confidence: 99%
“…The association of enteral feed initiation within 12 hours after birth with lower weight loss at 3 and 7 days of life suggests the benefits of EN on early neonatal growth. These findings are consistent with previous articles reporting that early EN shortens the time to regain birth weight in very preterm infants <32 weeks' GA. 13,19 Thus, early initiation of EN in moderate-to-late preterm infants may be a key intervention to reduce weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…3,10,11 Among very preterm infants <32 weeks' GA, caloric intake and protein intake have been suggested to be critical factors to promote growth and reduce risk of postnatal weight loss and morbidity. 12,13 These infants have higher baseline recommended intake due to their increased metabolic needs and low reserves. 14 The recommended caloric and protein requirements for preterm infants vary between 110 and 135 kcal/kg/d and 3.0 and 4.5 g/kg/d.…”
mentioning
confidence: 99%
“…Changes leading to BPD begin in utero and are affected by antenatal steroids, gestational age, birthweight, gender, maternal inflammation, and maternal BMI . BPD develops over the infant’s first several weeks, influenced by mechanical ventilation, excessive oxygen exposure, postnatal infections, nutrition and growth, and certain medications . These factors and others, share the common connection of propagation of pulmonary inflammation in the fetus and newborn.…”
Section: Hemodynamically Significant Pda and Bpdmentioning
confidence: 99%